EFFEK HEALTH EDUCATION PEMERIKSAAN SADARI SEBAGAI PENCEGAHAN DINI KANKER PAYUDARA PADA WUS DI PUSKESMAS MANGASA - Suhartatik, Suhartatik; Naharia Laubo,; Kurnia Rahma, (Journal of Innovation Research and Knowledge, 2025)
Breast cancer is one of the leading health problems with high incidence and mortality rates among women in Indonesia. Early detection through breast self-examination (BSE) is a simple, inexpensive, and effective method to reduce the risk of late diagnosis. However, awareness and practice of BSE among women of reproductive age remain low, including in the working area of Mangasa Primary Health Center, Makassar. This community service aimed to improve women’s knowledge and skills regarding BSE through health education. The method used was counseling with slide and video media involving 20 participants, accompanied by evaluation using pretest and posttest questionnaires. The results showed that before education, most participants (90%) had poor knowledge, 10% had fair knowledge, and none had good knowledge. After education, 95% of participants had good knowledge and 5% had fair knowledge, with none remaining in the poor category. This program also improved participants’ ability to perform BSE correctly. These findings indicate that health education is effective in enhancing knowledge and skills of women regarding BSE. Continuous education programs at primary health centers are essential as a preventive effort against breast cancer.